The effects of logistics-related knowledge management of courier service provider on e-business performance - Nurul Izzah, Mohd Shah (2018)
The rapid penetration of the Internet and smart-phones are accelerating the development of Malaysia’s courier and e-business industries, especially towards supporting each other. Ebusiness industry have been encouraging courier companies to develop more creative services to fulfill the requirements of partners by e-business companies. Nevertheless, to create services, the courier companies need to have efficient knowledge management processes in addition to managing logistics. However, there was lacking of sufficient guidance on bridging the gaps between logistics management, knowledge management and creativity, especially for both courier and e-business companies. Hence, the study mainly aimed to develop a novel logistics-related knowledge management framework towards ebusiness performance considering the mediating role of creativity as well as the moderating role of inter-firm dependence. A stratified random sampling and cross-sectional survey by 92 respondents from 14 courier companies was undertaken which had Creativity in Courier Services (C) and four determinants of Logistics-Related Knowledge Management (LRKM). There determinants were: logistics-related knowledge generation (LRKG), logistics-related knowledge dissemination (LRKD), logistics-related knowledge shared interpretation (LRKS) and logistics-related knowledge responsiveness (LRKR). Then, 92 respondents from 56 random selected E-business companies were surveyed on their financial performance (FP), e-business adoption level (EBL) and inter-firm dependence (IFD). The partial least square structural equation modeling was applied for data analysis using SmartPLS 3.0. The results demonstrated that among the factors of LRKM in courier companies, the LRKD was the most contributing factor that drove their e-business partner’s performance, followed by LRKR. Meanwhile, LRKG and LRKS are less contributing factors and were not significant. It was proved that creativity played a mediator role between the LRKM and E-Business Performance relationship. It was also found that IFD played the role of a moderator between the C and E-Business Performance relationship, it also strengthened the relationship. However, IFD did not mediate the relationship between LRKM and E-Business Performance. Hence, the implies: i) to enhance and help their partners’ e-business performances, the courier companies should continue focusing their efforts on both LRKD and LRKR, then invest more efforts on the least contributing factors of LRKG and LRKS, as which are part of the LRKM process and also contributing to E-Business Performance; ii) to further enhance E-Business Performance, courier companies should also invest in its C, which is a latent driver that facilitates E-Business Performance; and iii) to further assist the contribution of C onto ebusiness performance, more attention could be paid to IFD, in order to utilize its positive moderating effects. This research presents several theoretical contributions by providing further insights on determinants and outcomes of LRKM towards E-Business Performance, the importance of creativity of courier companies; the inter-dependence between courier companies and their e-business partners, especially in Malaysia. It is hoped that both industries could be better developed to boost Malaysia to become a fully developed nation by the year 2020.